The effect of nucleators on the quality of the surface of glass-ceramic denture coatings; Glass and Ceramics; Vol. 62, N 9-10 - Kulinich E. A. (2005, 2005)
The effect of nucleator additives on the surface relief and the degree of crystallization of material intended for the dentine and enamel layers of artificial denture is considered. It is established that hydroxyapatite additive is optimal for producing the required relief in the prime and dentine layers